Feasibility of microalgae as feedstock for alternative fuel in Malaysia: A review. (November 2020) - Hossain, Nazia; Hasan, M.H.; Mahlia, T.M.I.; Shamsuddin, A.H.; Silitonga, A.S.
Abstract: Biodiesel is an attractive fuel replacement for diesel engine in Malaysia. The application of biodiesel as fuel-blend has been implemented commercially in transport sector in the country. Among various potential feedstock for biodiesel production, microalgae have been appeared as a promising source since a decade due to its' high biomass productivity, rapid growth rate, large amount of lipid content, capability of high CO2 capture and sequestration as well as suitable geographical location to be harvested. The main objective of this study was to determine the feasibility of microalgae harvesting in Malaysia to produce biodiesel and potential to implement microalgae-biodiesel as commercial transportation fuel. This study demonstrated the current scenario of overall biodiesel production and application in Malaysia. Since Malaysia is the world's second-largest oil palm producer, exploitation of edible palm oil for the making of biodiesel is to be blamed as the cause of soaring food price; therefore, the country is currently looking for 3rd generation biofuel sources and microalgae has been preferred for this purpose. Therefore, insight of the significance of microalgae cultivation for this purpose, suitable microalgae candidates and possible feasibility of microalgae biodiesel have been delineated in this review study. Prospects and challenges to implement microalgae biodiesel have also been emphasized in this study. Therefore, the advantages and limitations of this biodiesel can be transparent to government and non-government sectors. Thus, this study can re-direct both sectors in future. Consequently, it may contribute setting an appropriate government policy to encourage microalgae for biodiesel production to sustain the local biofuel and secure economic growth, energy security and improve environmental conditions in near future. Highlights: Current scenario of biodiesel production and application in Malaysia. Technical viability and geographical suitability of microalgae harvesting for biodiesel. Feasibility of commercial microalgae biodiesel in Malaysia. Prospects and challenges for microalgal biodiesel implementation.